E-Modules Based on Contextual Wetlands to Improve Mastery of Physics Concepts of High School Students - Betty Lusiana; Fathurohman, Apit; Kistiono, Kistiono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
E-modules based on the wetland context represent one of the alternative teaching materials that can support the learning process. This study aims to develop a physics e-module contextualized with wetlands using Adobe Captivate software, with the goal of enhancing its effectiveness in classroom instruction. The research employed a Research and Development (R&D) approach conducted at SMA Negeri 1 Lempuing. The e-module was designed following the ADDIE development model, specifically for the topic of Archimedes’ Principle. The feasibility of the e-module was evaluated in terms of validity, practicality, and effectiveness. Validation results from media, content, and language experts yielded an average total score of 90.37%, categorized as very valid. Product trials with students resulted in a practicality score of 89.9%, indicating that the module was well-received. In terms of effectiveness, the e-module achieved an N-gain score of 0.64, which falls within the moderate category. These findings demonstrate that the developed e-module is valid, practical, and effective in improving high school students’ mastery of physics concepts.